Temporal trends of antibiotic resistance in culturable bacteria reveal the role of potential pathogens as pioneering carriers and resistance accumulators - Biyi Zhao; Wei Chen; Yanxia Ren; Liping Dai; Chaohui Tang; Xian Wang; Lingjie Xie; Yahao Huang; Yong Xiao (Environment International)
Understanding the occurrence and temporal trends of antibiotic resistance genes (ARGs) within bacteria is crucial for controlling and predicting the proliferation of antibiotic-resistant bacteria. However, gaps remain in understanding the long-term trends across different bacterial species and in assessing related health risks. We collected 22,360 bacterial complete genome sequences with collection time and compiled a temporal dataset of ARGs in culturable bacteria. Our results revealed the widespread presence of ARGs among culturable bacterial species, with potential pathogens carrying significantly more ARGs than non-pathogenic species. Temporal trend analysis revealed that only 11.0 % of bacterial species experienced an increase of more than one unit in ARG quantity and diversity over one century, with 83.3 % of them being potential pathogenic species. The temporal accumulation of ARGs in many potential pathogenic species is influenced by the abundance of mobile genetic elements, with several species also exhibiting temporal accumulation of plasmid-borne ARGs. Notably, Shigella flexneri and Klebsiella pneumoniae exhibited an accumulation of high-risk ARGs associated with at least five antibiotic types over at least 40 years. Furthermore, the distribution of ARG-carrying strains before the use of antibiotics revealed a wide range of bacterial species and antibiotic types for intrinsic resistance, including some synthetic antibiotics. This work reveals the significant role of potential pathogens in the expansion of antibiotic resistance and highlights the importance of strengthening vigilance against the emergence of novel multidrug-resistant pathogens.